2021
DOI: 10.36850/e3
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Joint Regeneration: How an Advanced Implant could Fail by Its In Vivo Proven Bone Component

Abstract: Articular cartilage damage is a major challenge in healthcare due to the lack of long-term repair options. There are several promising regenerative implant-based approaches for the treatment, but the fixation of the implant remains a significant challenge. This study evaluated the potential for repair of an osteochondral implant produced through a novel combined bioprinting-based chondral-bone integration, with and without cells, in an equine model. Implants consisted of a melt electrowritten polycaprolactone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…By using a custom-made compression head, the complete wedge underwent compression. Surface roughness was not assessed in this study, but previous in vivo studies using fibres of comparable thickness deposited using MEW showed no damage to the opposing structures in the joint ([ 37 ]). Lastly, overall tissue formation was limited in this study, which might be attributed to the low cell numbers, static culture conditions and absence of growth factor stimulation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By using a custom-made compression head, the complete wedge underwent compression. Surface roughness was not assessed in this study, but previous in vivo studies using fibres of comparable thickness deposited using MEW showed no damage to the opposing structures in the joint ([ 37 ]). Lastly, overall tissue formation was limited in this study, which might be attributed to the low cell numbers, static culture conditions and absence of growth factor stimulation.…”
Section: Discussionmentioning
confidence: 97%
“…PCL fibres are still present 6 months after implantation in and equine joint after extensive loading. This suggests suitability of the PCL scaffolds for clinical usage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their experiment Diloksumpan et al (2021) artificially damaged cartilage by drilling a hole in the joints of ponies, filled the gap with the construct that bears the cultured cartilage, and watched the outcome. To evaluate the results an admirable battery of well-chosen methods was applied to monitor the changes in biomechanical properties, biochemical composition (analysis of collagen and glycosaminoglycans), and morphology of the joints (radiography, microcomputed tomography, histology, and immunohistochemistry), and their function was established by following the walking behavior (gait analysis) of the ponies.…”
Section: Methodsmentioning
confidence: 99%
“…The paper by Diloksumpan et al (2021) in this issue of JOTE is a good example of this novel approach. The authors are involved in a study of the repair of damage of cartilage in bones and joints, using 3D-printed constructs; these serve as a scaffold on top of which new cartilage that has been grown in a cell culture system may be implanted inside the damaged site, leading to newly-formed cartilage growing from the implant.…”
Section: Introductionmentioning
confidence: 99%
“…While tested in vivo in a horse, results demonstrated successful mechanical stability and integration with surrounding native cartilage and bone tissues. [148] This interesting converged bioprinting and biomaterials approach shows promise for engineering mechanical competent soft-hard tissue interfaces. [147] Thus, we have exemplified how the combination of fiber or filament reinforcing technologies with extrusion based biofabrication techniques has proven to be an useful fabrication approach for the realization of 3D constructs that can approximate to the structural and mechanical functionality of native tissues.…”
Section: Role Of Converging (Bio) Fabrication Technologiesmentioning
confidence: 99%